Satisfactory Analysis of Training Program at Indonesian Railway Company: An Importance-Performance Analysis Approach - Romat Saragih; Mahir Pradana; Mahendra Fakhri; An Nisaa Intan (Integrated Journal of Business and Economics (IJBE), 2020)
Training is an activity that has an important role for human resources in order to increase knowledge and skills both for human resources who are preparing to enter the workforce, also for human resources who have worked so that their capabilities are always maintained in order to secure existence or to career advancement. From this research, we try to analyze the gap between perceptions and expectations of the training program in from the perspectives of the participants. The population of this study are 61 employees of PT Kereta Api Indonesia (Indonesian Railway Company) who were training participants at the Operations and Marketing Training Center. We analyzed the data by applying the Importance Performance Analysis (IPA) method. Based on the results of the research and descriptive analysis of the services received, the satisfaction of the operational training program is quite satisfying but there is still a difference between reality and employee expectations.